Analisis Rantai Markov Lima Status pada Return Harga Saham BBCA - Siti Sarah Sobariah Lestari; Ana Yuliana Jasuni (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
Stock is one of the most popular instruments traded in the capital market. Issuing shares is one of the choices made by companies when deciding to fund the company. In addition, stocks are an investment alternative that has been chosen by many investors because stocks are able to provide attractive returns. The movement of stock prices is a stochastic process, where today's price is affected by the previous day's stock price, and tomorrow's stock price is influenced by today's stock price. Thus, the movement of this stock price is a markov chain where the movement can occur repeatedly, but the exact time cannot be known. By studying the long-term behavior of the Markov chain, it is possible to predict stock movements in the future